Trends in therapeutic and prevention strategies for management of bovine mastitis: An overview - Tiwari, J.G.; Babra, C.; Tiwari, H.; Williams, Vincent; De Wet, S.; Gibson, J.; Paxman, Adrian; Morgan, Eleanor; Costantino, Paul; Sunagar, Raju; Isloor, Shrikrishna; Mukkur, Trilochan (Omics Publishing Group, 2013)
Mastitis is one of the most economically significant diseases for the dairy industry for backyard farmers in developing countries and high producing herds worldwide. Two of the major factors impeding reduction in the incidence of this disease is [a] the lack of availability of an effective vaccine capable of protecting against multiple etiological agents and [b] propensity of some of the etiological agents to develop persistent antibiotic resistance in biofilms. This is further complicated by the continuing revolving shift in the predominant etiological agents of mastitis, depending upon a multitude of factors such as variability in hygienic practices on farms, easy access leading to overuse of appropriate or inappropriate antibiotics at suboptimal concentrations, particularly in developing countries, and lack of compliance with the recommended treatment schedules. Regardless, Staphylococcus aureusand Streptococcus uberis followed by Escherichia coli, Streptococcus agalactiae has become the predominant etiological agents of bovine mastitis followed Streptococcus agalactiae, Streptococcus dysagalactiae, Klebsiella pneumonia and the newly emerging Mycoplasma bovis. Current approaches being pursued to reduce the negative economic impact of this disease are through early diagnosis of infection, immediate treatment with an antibiotic found to either inhibit or kill the pathogen(s) in vitro using planktonic cultures and the use of the currently marketed vaccines regardless of their demonstrated effectiveness. Given the limitations of breeding programs, including genetic selection to improve resistance against infectious diseases including mastitis, it is imperative to have the availabilityof an effective broad-spectrum, preferably cross-protective, vaccine capable of protecting against bovine mastitis for reduction in the incidence of bovine mastitis, as well as interrupting the potential cross-species transmission to humans. This overview highlights the major etiological agents, factors affecting susceptibility to mastitis, and the current status of antibiotic-based therapies and prototype vaccine candidates or commercially available vaccines against bovine mastitis as potential preventative strategies.